Implementasi Pembelajaran IPA Berbasis STEAM sebagai Upaya Meningkatkan PHBS Siswa dalam Pencegahan Penularan Penyakit - Laelatul Badriah; Muhammad Suwignyo Prayogo; Indi Putri Nurhidayah; Hanifa Abidah Faradis (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Clean and Healthy Living Behavior (PHBS) is an important preventive effort to reduce the spread of infectious diseases among school-age children. However, the implementation of PHBS among elementary school students still faces several challenges, including low awareness, lack of habituation, and learning processes that are predominantly focused on cognitive aspects. This study aims to describe and analyze the implementation of Science learning based on the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach in improving students' clean and healthy living behavior as an effort to prevent infectious diseases. This research employed a qualitative descriptive design. The study was conducted at Madrasah Ibtidaiyah Darul Ulum Jember in May 2026. Data were collected through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings revealed that STEAM-based science learning increased students' engagement in the learning process, strengthened their understanding of PHBS, and encouraged healthier behavior both at school and at home. The study also identified diverse responses from teachers and parents, initial resistance from some community members, and variations in students' academic achievement. Nevertheless, through socialization and support from various stakeholders, STEAM-based science learning was successfully implemented and positively contributed to the development of clean and healthy living behaviors. Therefore, the STEAM approach can serve as an effective alternative for integrating health education into science learning in elementary schools.